2017 ERS/ATS standards for single-breath carbon monoxide uptake in the lung. Issue 1 (3rd January 2017) - Graham, Brian L.; Brusasco, Vito; Burgos, Felip; Cooper, Brendan G.; Jensen, Robert; Kendrick, Adrian; MacIntyre, Neil R.; Thompson, Bruce R.; Wanger, Jack
This document provides an update to the European Respiratory Society (ERS)/American Thoracic Society (ATS) technical standards for single-breath carbon monoxide uptake in the lung that was last updated in 2005. Although both D LCO (diffusing capacity) and T LCO (transfer factor) are valid terms to describe the uptake of carbon monoxide in the lung, the term D LCO is used in this document. A joint taskforce appointed by the ERS and ATS reviewed the recent literature on the measurement of D LCO and surveyed the current technical capabilities of instrumentation being manufactured around the world. The recommendations in this document represent the consensus of the taskforce members in regard to the evidence available for various aspects of D LCO measurement. Furthermore, it reflects the expert opinion of the taskforce members on areas in which peer-reviewed evidence was either not available or was incomplete. The major changes in these technical standards relate to D LCO measurement with systems using rapidly responding gas analysers for carbon monoxide and the tracer gas, which are now the most common type of D LCO instrumentation being manufactured. Technical improvements and the increased capability afforded by these new systems permit enhanced measurement of D LCO and the opportunity to include other optional measures of lung function. Updated technical standards for measuring D LCO ( T LCO ) including the use of rapid gas analyser systems http://ow.ly/QUhv304PMsy